Criminogenic Factors Associated with Noncompliance and Rearrest of Mental Health Court Participants - Honegger, Laura N. (Criminal justice and behavior, 2019)
There is a considerable overrepresentation of individuals with mental health issues within the U.S. criminal justice system as compared with the general population. Mental health courts (MHCs) arose in response to this concern, with a primary aim of reducing recidivism. Thus far, MHC research has largely neglected the potential utility of criminogenic factors. A retrospective analysis of 163 MHC participants was conducted to examine the association between clinical and criminogenic factors and noncompliance, as well as for recidivism, using a series of Bayesian negative binomial regression models to compare predictors. Criminogenic factors, namely first offending prior to the age of 18, having a substance-related diagnosis, commission of a variety of crimes, historical probation or parole violation, and having less than a high school education were associated with an increased rate of engaging in noncompliant behavior and rearrest. None of the clinical factors were directly associated with noncompliance or rearrest outcomes.